A man named Doll - Ames, Jonathan (Mulholland Books/Little, Brown and Company, 2021)
From the creator of HBO's Bored to Death, a deliciously noir novel about idiosyncratic private detective Happy Doll and his quest to help a dying friend in a sun-blinded Los Angeles as "quirky, edgy, charming, funny and serious" as its protagonist (Lee Child). Happy Doll is a charming, if occasionally inexpert, private detective living just one sheer cliff drop beneath the Hollywood sign with his beloved half-Chihuahua half-Terrier, George. A veteran of both the Navy and LAPD, Doll supplements his meager income as a P.I. by working through the night at a local Thai spa that offers its clients a number of special services. Armed with his sixteen-inch steel telescopic baton, biting dry humor, and just a bit of a hero complex, the ex-cop sets out to protect the women who work there from clients who have trouble understanding the word "no." Doll gets by just fine following his two basic rules: bark loudly and act first. But when things get out-of-hand with one particularly violent patron, even he finds himself wildly out of his depth, and then things take an even more dangerous twist when an old friend from his days as a cop shows up at his door with a bullet in his gut. A Man Named Doll is more than just a fascinating introduction to one truly singular character, it is a highly addictive and completely unpredictable joyride through the sensuous and violent streets of LA.